F(x) = x + 4
g(x) = 2x - 3
(g - f)(2) = (2x - 3) - (x + 4)
(g - f)(2) = (2x - x) + (-3 - 4)
(g - f)(2) = x - 7
Answer:
9
Step-by-step explanation:
3x + 3 = 30
-3 -3
3x = 27
/3 /3
x= 9
Twice the difference between x and k is 2(x-k)
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
<span>P(t) = Po(1 - r)^t
P(t) = price after t months --> S
Po = initial price -- P
r = rate as a decimal
S = P(.9)^4
-> = 100(.9)^4
-> = 65.61
(100 - 65.61)/100
34.39/100
34%</span>
The national interest rate on houses for 25 years is 4.3%. The banker wishes to test that the local interest rates are lower than the national rate. So he should use the initial data of 4.3% interest as his base data. Then he should investigate the rates of houses in the local vicinities and compare it to his base data.